2016
DOI: 10.1002/jbm.a.35670
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of bone formation during fracture healing by poly(pro–hyp–gly)10 and basic fibroblast growth factor containing polycystic kidney disease and collagen‐binding domains from Clostridium histolyticum collagenase

Abstract: Growth factor delivered in combination with animal-derived collagen materials has been used to accelerate bone fracture healing in human patients. However, the introduction of bovine proteins into humans carries the risk of zoonotic and immunologic complications. Here, we developed a collagen-like polypeptide-based bone formation system consisting of poly(Pro-Hyp-Gly)10 , which mimics the triple helical conformation of collagen, and basic fibroblast growth factor (bFGF) fused to the polycystic kidney disease (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…Growth factors, which stimulate cellular proliferation and/or differentiation, have also been shown to accelerate fracture healing. Mitogenic activity of basic fibroblast growth factor (bFGF) has been proven to be effective when combined with a proper carrier or other system for sustained release . Platelet‐derived growth factors (PDGFs) from blood plasma have been used to augment bone formation and bone defect repair, especially in dentistry .…”
mentioning
confidence: 99%
“…Growth factors, which stimulate cellular proliferation and/or differentiation, have also been shown to accelerate fracture healing. Mitogenic activity of basic fibroblast growth factor (bFGF) has been proven to be effective when combined with a proper carrier or other system for sustained release . Platelet‐derived growth factors (PDGFs) from blood plasma have been used to augment bone formation and bone defect repair, especially in dentistry .…”
mentioning
confidence: 99%
“…Collagen materials have been used for the sustained release of rhBMP-2 in clinical settings [9][10][11]. We previously reported that collagen-like polypeptide poly(POG)n is superior to animalderived collagen with regard to thermal stability and lack of pathogenicity and is a useful carrier which retains bFGF well [17,18]. Our preliminary study showed that 2.0 μg of rhBMP-2 without poly(POG)n failed to promote bone formation in a mice bone defect model.…”
Section: Implants Segmental Mousedismentioning
confidence: 87%
“…We previously reported that the artificial collagen-like peptide poly(POG)n was a useful carrier for growth factors. Injection of bFGF-loaded poly(POG)n into fracture sites stimulated periosteal bone formation in mouse fracture models [17,18]. In the present study, we investigated whether a single injection of rhBMP-2-loaded artificial collagen-like peptide gel (rhBMP-2/ACG) accelerates consolidation at the bone defect site and bone union at the docking site in a mouse SBT model.…”
Section: Introductionmentioning
confidence: 98%
“…Images of the entire femur were first obtained, and 10 mm regions of interest (500 slices) were defined at the midfemur. New bone volume and bone mineral content were measured using three-dimensional (3D) image analysis software (Tri-3D-Bon; Ratoc System Engineering Co., Ltd., Tokyo, Japan) as previously described [28, 31]. …”
Section: Methodsmentioning
confidence: 99%